Perancangan Sistem Penilaian Siswa Didik (PENSIDIK) Berbasis Web - Mayadi; Nirmala, Indah Dwijayanthi (Journal of Informatic and Information Security, 2020)
SMAN 1 Cibitung in the process of processing data on the results of evaluating student learning scores is still using manually and stored in separate files / data. Where this becomes an obstacle in ineffective and inefficient data processing. Related to this, the purpose of this study is to develop a system design in the process of processing data on student learning outcomes effectively and efficiently based on web. In this study using a systematic approach, namely the waterfall method. Based on the results of the study, it is necessary to design an information system for processing student grade data in order to facilitate operational management activities for processing school student value data to be utilized by SMAN 1 Cibitung.